The Dual Descriptor Reveals the Janus–Faced Behaviour of Diiodine - Martínez-Araya, Jorge I. (Frontiers in Chemistry, 2022)
The Janus–faced ligand behavior of diiodine (I2) was evidenced after applying the dual descriptor (DD or second-order Fukui function), thus providing additional support to the work performed by Rogachev and Hoffmann in 2013. Along with its capacity to reveal sites susceptible to undergo attacks simultaneously of nucleophilic and electrophilic types, another advantage of DD lies in being an orbital-free descriptor. That means it is based only upon total electron densities when written in its most accurate operational formula. This quality is not exclusive of DD because when Fukui functions are written in terms of electron densities instead of densities of frontier molecular orbitals, they become orbital-free descriptors too. Furthermore, the present work is an application of the generalized operational formula of the dual descriptor published in 2016 that takes into account any possible degeneracy in frontier molecular orbitals. As a proof about capabilities of DD, the possible sites for a favorable interaction between I2 with two organometallic compounds [Rh2(O2CCF3)4] and [(C8H11N2)Pt (CH3)] were correctly revealed by overlapping the biggest lobe for receiving nucleophilic attacks of one molecule with the biggest lobe for receiving electrophilic attacks of the other molecule, so allowing to predict the same coordination modes as experimentally known: linear “end–on” for the [(C8H11N2)Pt (CH3)]…I2, and bent “end–on” for the [Rh2(O2CCF3)4]…I2 interactions.